TRAINING AL-QUR’AN DAN INTEGRASI ILMU PENGETAHUAN DI YAYASAN BALQIS, JAKARTA - Muhammad Adlan Nawawi; Nur Hidayaturrohmah; Baeti Rohman; Abdur Rokhim Hasan; Andi Rahman; Habil Abyad (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2024)
This research analyzes the integration of science and religion from an Islamic perspective, focusing on theological foundations, historical dynamics, and its relevance to contemporary civilization. The objective is to examine the concept of integration as a solution to the dichotomy between religious and secular sciences and its impact on the progress of Muslim societies. The research method employs a descriptive approach. Findings indicate: First, the integration of science and religion is an essential foundation in Islam originating from the first revelation (Surah Al-Alaq (1-5), rejecting dichotomies and emphasizing knowledge as a means to strengthen faith. Second, the zenith of Islamic civilization during the Umayyad-Abbasid era (with figures like Ibn Sina and Al-Khwarizmi) was built upon this integrative paradigm, yet declined after the fall of Baghdad (1258 M), triggering an atomistic dichotomy. Third, contemporary thinkers' efforts to revitalize integration aim to counter the hegemony of secular ideologies and the moral crisis in modern science. Furthermore, integration is not merely a theoretical concept but a key instrument for building a sustainable civilization that combines scientific advancement with Qur’anic ethics. This study contributes to educational discourse, scientific policy, and strengthening Muslim identity amid global challenges, offering a model for harmonizing science and religion within the Qur’anic framework